(untitled) (Eurasian Medical Research Periodical, 2023)
The genus. Klebsiella is a gram negative bacteria belonging to the family of. Enterobacteria. These bacteria’s natural habitat is the human and animal intestinal tract, but they were the causative agent a range of respiratory and urinary tract the infections, bacteremia, and burn and wound smears so are typical bacteria that may colonize both people and animals and cause both of them to get seriously ill. Due to their high the level of adaptation to environmental and synthetic circumstances and their capacity that to acquire antimicrobial and metal. Biocide resistance determinants,bacteria Klebsiella organisms typically exhibit by resistance to various antibiotics. The current study includeincludeed eighty (80) Klebsiella spp. Various types of samples were collected during 10. 2021, from hospital laboratories of Al-Sadr in HolyNajaf, Iraq. A statistical analysis of antibiotic resistance in bacteria revealed the most effective antibiotics, are Tetracyclines, Ertapenem, Amikacin, imipenem, and Gentamycin this analysis reveal different percentages. The study also showed that females have a higher infections rate (66.3%) higher than infection rates of males ( 33.7%). The study conducted on various samples. However, the majority are urine samples 57.5%. Finally, current study found that the infection rate increased during the summer more than other seasons.